Learning outcomes of project-based learning activities on access to functional diversity terms - Campoy-Cubillo, Mari Carmen (Frontiers in Education, 2025)
IntroductionThis article presents a project-based classroom practice of transformative language teaching and learning for sustainability (TLS). Sustainable Development Goal 10 (SDG10) was approached paying close attention to the use of language in relation to (in)equality-related terms. This use of language is also defended as SDG18 in recent research in a debate about the importance of language use as a transversal sustainable development goal.MethodologyA task-based methodology is employed to examine students’ perception on functional diversity terms and how their understanding changed throughout the practice developed in the study. Qualitative data in this study are drawn from a group of students (n = 20) who were finishing their degree in English Studies. Students participated in a task to analyze five functional diversity terms (Special Educational Needs, disability, deaf, blind, and Asperger’s). A qualitative research questionnaire asked the participants to reflect on their learning process in this task.Results and discussionThe report of our findings shows how students developed their lexicographic and conceptual competence regarding FD terms. Results illustrate how TLS transformed students’ concepts and ideas underlying functional diversity concepts and helped promote sustainable language use.